2021
DOI: 10.3390/ijerph18052409
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nordic Walking on Isokinetic Trunk Muscle Endurance and Sagittal Spinal Curvatures in Women after Breast Cancer Treatment: Age-Specific Indicators

Abstract: Nordic walking (NW) is a popular form of rehabilitation. NW improves psychophysical condition in breast cancer (BC) survivors. This study aimed to analyze the effects of NW on functional and postural changes of the trunk in women of different ages after BC. We hypothesized that an age relationship would be found. BC survivors (n = 39) were stratified by age as “middle- aged” (45–59 years) or “older” (60–75 years), then randomly allocated to the training intervention. A study group (SG, n = 19) participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The results of insignificant changes of spinal posture in this study are consistent with two previous studies, which found that 6-8 weeks of Nordic walking training did not significantly alter spinal posture during walking in healthy, older adults [16] and elderly women with Parkinson's disease [18]. In contrast, a previous study showed that, compared to general gymnastics, eight weeks of Nordic walking training significantly reduced thoracic kyphosis of middle-aged women after breast cancer treatment [17].…”
Section: Spinal Posturesupporting
confidence: 91%
See 2 more Smart Citations
“…The results of insignificant changes of spinal posture in this study are consistent with two previous studies, which found that 6-8 weeks of Nordic walking training did not significantly alter spinal posture during walking in healthy, older adults [16] and elderly women with Parkinson's disease [18]. In contrast, a previous study showed that, compared to general gymnastics, eight weeks of Nordic walking training significantly reduced thoracic kyphosis of middle-aged women after breast cancer treatment [17].…”
Section: Spinal Posturesupporting
confidence: 91%
“…Nordic walking requires the forward inclination of the trunk, resulting in a smaller trunk flexion angle [16] and increased activation of the trunk muscles [30]. However, there are limited scientific reports examining the effect of Nordic walking on spinal posture in older adults [16][17][18]. The results of insignificant changes of spinal posture in this study are consistent with two previous studies, which found that 6-8 weeks of Nordic walking training did not significantly alter spinal posture during walking in healthy, older adults [16] and elderly women with Parkinson's disease [18].…”
Section: Spinal Posturementioning
confidence: 99%
See 1 more Smart Citation
“…Among the recently discussed breast cancer issues is the postural control assessment in women after mastectomy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. A review of the above-mentioned publications indicated that the undertaken research was concerned with the impact of mastectomy on body static conditions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and body posture of women who had received mastectomies [ 7 , 10 , 18 , 19 ,…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies assessing posture in athletes have indicated specific spinal adaptations in several types of athletes such as volleyball players ( Grabara, 2020 ; Grabara, 2015 ), handball players ( Grabara, 2014a ), basketball players ( Grabara, 2016 ), cyclists ( Muyor, Lopez-Minarro & Alacid, 2011 ), skiers ( Alricsson & Werner, 2006 ), rhythmic gymnasts ( Kums et al, 2007 ), dancers ( Kruusamae et al, 2015 ), hockey ( De Baranda et al, 2020 ) and wrestlers ( Rajabi et al, 2008 ). Specific exercise programs or other forms of PA such as Nordic Walking ( Hanuszkiewicz, Wozniewski & Malicka, 2021 ), Pilates ( González-Gálvez et al, 2020 ) a hatha yoga can also have an influence on posture.…”
Section: Introductionmentioning
confidence: 99%